Black Poetic Inquiry - Alexander, Bryant Keith, 1963- author. Link
1 online resource (202 pages).
Keywords: The poems in this project were written within a 24-hour period of each other and are presented in order of their appearance for the month of January 2024. Written as a call and response to each other, the poems are at times direct responses in content and form, or a mediation on what the offering triggered in the other. Using poetry writing as a methodological engagement with the reflective and reflexive attributes of autoethnography, this project offers an examination of lived experience and will provide a critical expansion of poetic inquiry. An example of "collaborative spirit-writing," this text uses a dialogical exchange of responsiveness, excavating the lived experiences of the two authors (a Black man and a Black woman) with complex intersectional identities. Using poetic writing as both form and function, this book provides a performance of remembrance and resistance.Students and researchers working with qualitative inquiry and in areas from performative writing to Critical Race Studies will find this book a useful addition to their research. Teachers will also find this book facilitates pedagogies of engagement.